2003
DOI: 10.1007/s11910-003-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic complications of chemotherapy for children with cancer

Abstract: Survival rates for children with cancer have increased dramatically over the past few decades. Development of new chemotherapeutic agents and the expanded use of older agents have had a major impact on this celebrated improvement. Chemotherapy can have, however, significant toxicity on the nervous system. The most common neurologic complications involve acute alterations in consciousness, leukoencephalopathy, seizures, cerebral infarctions, paralysis, neuropathy, and ototoxicity. Most of the information on tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…These data have led the American Academy of Pediatrics (AAP) to recommend consistent screening of infants and young children up to 5 years of age (AAP Committee on Children With Disabilities, 2001; Council on Children With Disabilities, Section on Developmental Behavioral Pediatrics, Bright Futures Steering Committee, Medical Home Initiatives for Children With Special Needs Project Advisory Committee, 2006). The neurodevelopmental effects of chemotherapy agents can cause subtle delays in the course of overall development that otherwise may be amendable to supportive developmental therapies, which can maximize the quality of life for children affected by pediatric cancer (Bornstein et al, 2012; Reddy & Witek, 2003). The Children’s Oncology Group (COG) reports that 80% of children diagnosed with cancer survive at least 5 years, and two thirds of survivors experience at least one neurocognitive effect of therapy (Nathan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These data have led the American Academy of Pediatrics (AAP) to recommend consistent screening of infants and young children up to 5 years of age (AAP Committee on Children With Disabilities, 2001; Council on Children With Disabilities, Section on Developmental Behavioral Pediatrics, Bright Futures Steering Committee, Medical Home Initiatives for Children With Special Needs Project Advisory Committee, 2006). The neurodevelopmental effects of chemotherapy agents can cause subtle delays in the course of overall development that otherwise may be amendable to supportive developmental therapies, which can maximize the quality of life for children affected by pediatric cancer (Bornstein et al, 2012; Reddy & Witek, 2003). The Children’s Oncology Group (COG) reports that 80% of children diagnosed with cancer survive at least 5 years, and two thirds of survivors experience at least one neurocognitive effect of therapy (Nathan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Cranial RT as well as intrathecal chemotherapy results in these complications. [12][13][14][15] Comparison of the effects of various therapeutic approaches has resulted in reduction in the neurotoxicity of various regimens. 8,16 Brouwers and Poplack 17 reported that attention deficits represented the main variable by which diminished skills in memory tests could be explained in ALL patients.…”
Section: Introductionmentioning
confidence: 99%
“…This case was used to springboard into a the following discussion of possible contributing factors. An AIDP presentation has been described as both a paraneoplastic phenomenon as well as associated with complications of chemotherapy (Reddy, 2003 …”
Section: Case #5mentioning
confidence: 99%
“…It tends to spare pain and temperature modalities (Reddy, 2003). Studies in adults have demonstrated accumulation of cisplatin in the dorsal root ganglia of patients undergoing this treatment (Thompson, 1984).…”
Section: Emg/ncv Findingsmentioning
confidence: 99%